Content validation of a catalog of exercises for judo - Pedrosa, G. F.; Soares, Y. M.; Gonçalves, R.; Couto, B. P.; Dias, R. A.; Costa, V. T.; Kalina, R. M.; Szmuchrowski, L. A. (Perceptual and Motor Skills, 2016)
This study aimed to assess the content validity of a catalog of 76 judo exercises. Two groups of raters comprising 16 judo experts evaluated the following content validity indicators: Clarity of Language, Practical Pertinence, Theoretical Relevance, and the Dimension of each exercise. The results confirmed the content validity of the judo training catalog with indicators showing scores greater than 0.80. These findings suggest that all 76 judo exercises are pertinent, representative of judo training and understandable for judo coaches. Thus, this catalog of judo exercises may help judo coaches in the selection and recording of exercises. ABSTRACT FROM AUTHOR